Health Education Wound Care On The Readiness Of First Aid To Students And Teachers Of SMP 47 Palembang - Eva susanti; Selvya Muqitasyari; Indah Rahmasari; Nabila Verdina (CV. AFDIFAL MAJU BERKAH, 2024)
Indonesia is the fifth country with the highest accident rate. Accidents can happen to anyone, anytime, and anywhere, including at school, which can also cause acute injuries such as lacerations or bruises. The severity of injuries resulting from accidents, apart from being determined by the potential for accidents, can also be determined by the level of knowledge and attitude in providing first aid. First aid in accidents (P3K) is aimed at providing emergency care or first aid for victims before further assistance is provided by other health workers. Objective: To determine the readiness of students at SMP N 47 Palembang to treat injuries resulting from accidents regarding their level of knowledge and attitude. first aid for PMR cadres at SMP N 47 Palembang. Research Design: This community service design uses a quasi-experiment prepost-test without control. The knowledge instrument for this community service uses the First Aid questionnaire to assess knowledge. The results of the reliability test were carried out on 10 students at SDN Rumpet Krung Barona Jaya with a score of 0.72 (good level of reliability). The normality test using the Shapiro-Wilk tests (p<0.05) stated that the data was not normally distributed so this study used the Wilcoxon test analysis. Analysis of this community service data uses a computerized statistical analysis program. Conclusion: There is an influence of health education for treating accident injuries on the level of first aid knowledge and attitudes among PMR cadres at SMP N 47 Palembang.